The intersection of intimate partner violence with sexual reproductive health in the Pacific: findings from a Kiribati population study - Anneliese Spiteri-Staines; Luz Viviana Sastre Gomez; Jess Letch; Anna Bornemisza; Kristin Diemer (BMC Women's Health)
Abstract Background Women who experience intimate partner violence (IPV) are likely to experience reduced sexual and reproductive health (SRH). This paper aims to describe the prevalence of IPV and family planning use, and explore how IPV intersects with SRH among young Kiribati women; including met and unmet need for family planning, and use of contraception. Methods Data for this paper were drawn from the Kiribati Social Development Indicator Survey [1], conducted in 2018–2019. Chi-square tests for independence were conducted, with 95% confidence intervals to identify the strength of association. Associations were considered statistically significant at p < .05. Results Of the n = 3,106 women who had been intimately partnered or sexually active in the last year, 20% had unmet need for either spacing or limiting, the greatest unmet need being observed in women aged 15–24 years (28.8%). Half (51%) of ever-partnered Kiribati women experienced physical IPV from an ex/partner in their lifetime, one quarter experienced sexual IPV (24%) and 46% psychological IPV. Women aged 15–24 years reported higher rates of physical and/or sexual IPV over their lifetime and within the last year. Women who had experienced IPV from their partner in the last 12 months were significantly less likely to show unmet need for spacing or limiting (46.5%) than women who had not experienced any IPV (53.5%) and were more likely to be using a modern method of contraception (31%) than women who had not experienced IPV (26%). Women who experienced lifetime IPV were more also more likely to report met need for family planning. Conclusions This study shows women in Kiribati experience elevated rates of IPV and unmet need for family planning. Inclusion of young women (including single women) and rural women, especially women living with IPV must be prioritised as an international goal if the SRH needs are to be met for all. In order to overcome the difficulties faced by young women, women in remote areas and those experiencing IPV, health-care providers would benefit from further training and information on the issues around IPV.